PENGARUH ELECTRONIC WORD OF MOUTH DAN BRAND IMAGE TERHADAP MINAT BELI SABUN PEMBERSIH WAJAH WARDAH DI KOTA BATAM - Putri, Helmilia; Suhardi, Suhardi (LPPM Universitas Putera Batam, 2025)
The purpose of this study is to investigate how Batam City people's interest in purchasing Wardah face wash products is influenced by brand image and electronic word-of-mouth (eWOM). Consumer reviews on social media and internet platforms are a significant component in influencing consumers' shopping decisions in the current digital era. Additionally, building favorable opinions and boosting consumer interest in a product are significantly influenced by brand image. In this study, Wardah customers in Tiban, Batam City, were given a distributed survey using a quantitative methodology. The dependent variable is purchase interest, and multiple linear regression is used to examine the partial and simultaneous effects of the independent variables (electronic word-of-mouth and brand image). The study's conclusions demonstrate that brand image and electronic word-of-mouth have a favorable and significant influence on Batam City residents' interest in purchasing Wardah face cleanser. The results of this study should help businesses create more successful marketing plans, particularly when it comes to using digital communication's power and enhancing brand perception.